Uncertainty derived from elemental analysis and its effect on the separation of radioactive waste into low-level radioactive waste and waste for clearance. (January 2021) - Kinoshita, Norikazu; Noto, Takuma; Kosako, Kazuaki; Asada, Motoyuki; Torii, Kazuyuki; Tada, Akane; Urabe, Kohei; Ohtsuki, Tsutomu; Sekimoto, Shun
Abstract: Radioactive cobalt (Co), cesium (Cs), and europium (Eu), produced by neutron-capture reactions of the corresponding trace elements, are the main radioactive components of concrete waste in the decommissioning of aged nuclear power stations. The uncertainty regarding the activity of individual nuclide produced by activation is a main factor for efficient separation of radioactive wastes. Major and trace elements in the geostandard reference JG-3, aggregates collected from quarries, and cements, were analyzed by four different methods to evaluate experimentally the uncertainty. Neutronactivation analysis, a non-destructive technique, and analysis by using instruments such as an inductively coupled plasma mass spectrometry (ICP-MS) following sample digestion by alkali fusion have uncertainties of 30% for the content of major and trace elements. ICP-MS measurements following digestion by HF or K2 S2 O3 showed a poorer precision, especially for the trace elements. The Monte Carlo simulation using PHITS code was performed to estimate the depth profiles and uncertainty for the radionuclides produced by activation in the concrete including the uncertainty derived from the elemental analyses and local variability. On the basis of the uncertainty, we evaluated the boundary depth between low-level radioactive waste and waste for clearance in a bioshield for the prudent separation. Graphical abstract: Image 1 Highlights: The uncertainty of elemental composition is important for efficient separation of radioactive waste. Major and trace elements in standard reference material, aggregates and cements were analyzed. The accuracy and uncertainty of the elemental composition by the analyses were evaluated. The amounts of the products were simulated in consideration of the uncertainty in the elemental composition. The location for the prudent separation of radioactive wastes was evaluated based on the uncertainty.